Air travel can be safe and well tolerated in patients with clinically stable pulmonary hypertension - Thamm, Melanie (Medknow Publications, 2011)
Our aim was to determine what proportion of patients with pulmonary hypertension (PH) has undertaken air travel contrary to the general medical advice and to characterize these patients according to disease severity and medical treatment. In cooperation with Pulmonale Hypertonie e.V., the German patient organization, a questionnaire was distributed. In total, 430 of 720 questionnaires were returned completed. Of the 179 patients who travelled at least once by air, the distribution of New York Heart Association functional classes I/ II/ III/ IV was 2/ 77/ 74/ 8, respectively; 83 patients were receiving monotherapy; 58 patients were receiving a combination of two or more therapies; 57 patients were on long-term ambulatory oxygen treatment; and 29 patients used supplemental oxygen while travelling. Overall, 20 adverse events were reported, mostly of mild to moderate severity (i.e., peripheral edema, dyspnea), with need of medical intervention in only 7 cases. The 251 patients who did not travel by air were, on average, in more advanced stages of disease and/or clinically unstable. In conclusion, a majority of patients (159 out of 179) did not experience any complications during or directly after the flight even though no special precautions were taken. Thus we conclude that for patients with PH in a stable clinical condition, air travel can be safe and well tolerated.